2018
DOI: 10.1177/2331216518800640
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Subjective Tinnitus and Cervical Spine or Temporomandibular Disorders: A Systematic Review

Abstract: Movements of the neck and jaw may modulate the loudness and pitch of tinnitus. The aim of the present study was to systematically analyze the strength of associations between subjective tinnitus, cervical spine disorders (CSD), and temporomandibular disorders (TMD). A systematic literature search of the Medline, Embase, and Pedro databases was carried out on articles published up to September 2017. This covered studies in which tinnitus and CSD or TMD were studied as a primary or a secondary outcome and in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 60 publications
(187 reference statements)
2
35
0
2
Order By: Relevance
“…© 2019 Polish Dental Association than two symptoms of TMD (compared to 35% of patients in a tinnitus-free control group) and that among TMD patients from 7% to 60% had tinnitus, according to different studies [24]. Higher prevalence of tinnitus in TMD patients was also observed in other studies, supporting the hypothesis that TMD may play a causal role in the development of tinnitus [2,16]. However, it seems that there are no significant patterns of correlation with specific TMD [13].…”
Section: R E V I E W Pa P E Rsupporting
confidence: 52%
“…© 2019 Polish Dental Association than two symptoms of TMD (compared to 35% of patients in a tinnitus-free control group) and that among TMD patients from 7% to 60% had tinnitus, according to different studies [24]. Higher prevalence of tinnitus in TMD patients was also observed in other studies, supporting the hypothesis that TMD may play a causal role in the development of tinnitus [2,16]. However, it seems that there are no significant patterns of correlation with specific TMD [13].…”
Section: R E V I E W Pa P E Rsupporting
confidence: 52%
“…Interestingly, prevalence of tinnitus in patients with TMJ disorders reaches 60% in comparison to 15–30% in patients with no TMJ disorder (Chole and Parker, 1992; Tuz et al, 2003). The association between tinnitus and TMJ disorders was confirmed by two recent systematic reviews that reported a significant association between the two conditions in the majority of the identified studies (Bousema et al, 2018; Mottaghi et al, 2019). Both reviews assessed the quality of the included studies.…”
Section: Introductionmentioning
confidence: 61%
“…Quality ranged from low to high indicating some risk of bias in reported findings. Bousema et al (2018) evaluated 22 studies which investigated the presence of cervical spine disorders (CSDs) or TMJ disorders in patients with and without tinnitus, or the presence of tinnitus in patients with and without TMJ disorders. In contrast, Mottaghi et al (2019) evaluated findings from just five studies comparing patients with and without TMJ disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies were conducted to understand the relationship between otoneurological symptoms and TMDs, and these studies showed that the head position influences the mandibular resting position, thereby increasing muscle tension 5 . In addition, most patients with tinnitus, headache, and dizziness presented abnormalities during mandibular movement 6,7 , dislocated articular disk 8 , and abscesses or diseases of the dental pulp due to bruxism 9 .…”
Section: Introductionmentioning
confidence: 99%